BALANCING CAREER AND PERSONAL LIFE: BUSINESS MANAGEMENT CHALLENGES FOR MUSLIM WOMEN IN BANYUWANGI REGENCY - Rosyidi, Leili Hidayati; Asnawi, Nur; Khasanah, Umrotul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
The challenges faced by Muslim women in balancing their careers and personal lives, especially in the context of Banyuwangi Regency, can be diverse. Studies from Bangladesh and Malaysia highlight common barriers such as lack of finances, gender bias, work-life balance issues, and social norms. Successful Muslim women entrepreneurs emphasized the importance of faith, worship, and morality in managing their businesses effectively, demonstrating the importance of Islamic values in entrepreneurship. Strategies such as flexibility, family support, organizational support, time management, stress management, and maintaining good relationships with stakeholders emerged as important factors to achieve work-life balance and overcome challenges in a patriarchal society such as Banyuwangi Regency. Understanding these dynamics is essential to empowering Muslim women in Banyuwangi Regency to navigate the complexities of business management while maintaining personal well-being.